Development of Fourier Transform Infrared Spectrophotometric Method for Quantification of Simvastatin, Atorvastatin, and Rosuvastatin in Marketed Tablet Preparations - Nerdy, Nerdy; Zebua, Nilsya Febrika; Nadia, Syarifah; Putra, Effendy De Lux; Bakri, Tedy Kurniawan (Molekul, 2025)
ABSTRACT. Marketed pharmaceutical dosage forms must be checked to ensure that the drug in distribution meets the quality requirements. The Fourier transform infrared spectrophotometric method will provide new innovations which are low cost, environmental friendly, simple, and rapid for analysis. The aim of this research was to develop a single analytical method that can be used to determine levels of three different statin derivatives (simvastatin, atorvastatin, and rosuvastatin) in tablet preparations. The method used in this study was Fourier transform infrared spectrophotometric, a very simple sample preparation stage by solvent extraction with minimal solvent extraction without potassium bromide and without pellet press. The specific wave numbers of simvastatin, atorvastatin, and rosuvastatin were determined between 4000 cm–1 to 650 cm–1. The Fourier transform infrared spectrophotometric method had been successfully developed and successfully applied to the determination of levels of simvastatin, atorvastatin, and rosuvastatin in marketed tablet preparations containing single active pharmaceutical ingredient. The specific wave numbers of simvastatin, atorvastatin, and rosuvastatin obtained was 1712.7 cm–1; 1660.5 cm–1; and 965.4 cm–1, respectively. The results obtained in the content determination based on the peak height and peak area fulfill the requirements for active pharmaceutical ingredient assay ranging from 90.00% to 110.00%. The developed method has also been validated for accuracy, precision, specificity, linearity, range, limit of detection, and limit of quantitation. Thus, this method can be a valid alternative method, cheap, green, easy, and fast in determination of the levels of simvastatin, atorvastatin, and rosuvastatin in tablet preparations. Keywords : atorvastatin, FTIR, rosuvastatin, simvastatin, tablet